Using the Sherrod model in predicting financial failure in Iraqi private banks: an applied study in the Iraqi commercial and Iraqi Islamic banks (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:              The phenomenon of financial failure is one of the phenomena that requires special attention and in-depth study due to its significant impact on various parties, whether they are internal or external and those who benefit from financial performance reports. With the increase in cases of bankruptcy and default facing companies and banks, interest has increased in understanding the reasons that led to this financial failure. This growing interest should be a reason to develop models and analytical methods that help in the early detection of this increasing phenomenon in recent year   . The research examines the use of Sherrod's model in predicting financial failure in Iraqi private banks. The researchers relied on this mathematical model to analyze financial data and estimate the probability of financial failure occurring in these banks. Financial data was collected for a sample of private banks in Iraq over several years, and these data were used to apply the Sherrod model. As for the sample, a sample was chosen from the research consisting of two banks (the Commercial Bank of Iraq and the Iraqi Islamic Bank) for the research and a time series that extended for five years (2017 – 2021) , The results showed that the Sherrod model has a good ability to predict financial failure in Iraqi private banks. The researchers used a variety of financial and accounting variables in the model, which contributed to improving the accuracy of predicting financial failure.    This study represents an important contribution to understanding how mathematical models such as Sherrod's model can be used to estimate the risk of financial failure in banks. These tools help guide strategies and make sound financial decisions. This research is considered an important step towards improving the sustainability and performance of private banks in Iraq and enhancing confidence in the financial system.